Optimization of DNA extraction of physic nut (Jatropha curcas) by selecting the appropriate leaf - EDI PRAYITNO; EINSTIVINA NURYANDANI (Smujo International, 2011)
Abstract. Prayitno E, Nuryandani E. 2011. Optimization of DNA extraction of physic nut (Jatropha curcas) by selecting the appropriate leaf. Nusantara Bioscience 3: 1-6. Jatropha curcas L. has important roles as renewable source of bioenergy. The problem occurs on difficult of DNA extraction for its molecular breeding programs. The objectives of this research were to study which leaf best as source of DNA extraction. Four accessions were used, namely J1 and J2 (Jawa Tengah), S1 (South Sumatra), and S2 (Bengkulu). First, third, fifth, seventh, and yellow leaves for each accession were extracted using modification of Doyle and Doyle (1987) method. Visualization and comparison with Lambda DNA, Spectrophotometer UV-Vis and cutting DNA with EcoRI enzyme were show quality and quantity of DNA. The result showed that third leaves have sufficient quality and quantity as source of DNA. Third leaves DNA quantity for J1 (19.33 µg/mL), J2 (26.21 µg/mL), S1 (31.20 µg/mL), and S2 (61.03 µg/mL), and quality for each accession were 1.9063 (J1), 2.0162 (J2), 2.0116 (S1), and 2.0856 (S2).